ESTROGEN-TESTOSTERONE RATIO IN PLEXUS PAMPINIFORM OF NORMAL RABBITS AND RABBITS WITH LEFT ARTIFICIAL VARICOCELE - Simorangkir, Lambok; Sihombing, Aaron T.; Noegroho, Bambang S. (Indonesian Urological Association, 2013)
Objective: To evaluate estrogen-testosterone ratio in rabbits with a left artificial varicocele. Material& Method: Eight rabbits were divided into two groups.The first group underwent ligation of left renal vein to induce artificial varicocele and the second group underwent a sham operation as control group. Eight week after ligation, blood samples were taken from the pampiniform plexus in both groups. Serologic examination (ELISA) was performed to measure testosterone and estrogen level. The t-test was used to compare the differences of the estrogen-testosterone ratios, a p value < 0,05 is considered significant.Results: Testosterone level was increased with 279% and estrogen level was increased with 33% blood from the pampiniform plexus in group 1 compared with group 2 (normal rabbits). The ratio of estrogen-testosterone between the control group and the artificial varicocele group were 1 : 3. Differences of the ratio between two groups were statistically significant (p < 0,05). Conclusion: Estrogen-testosterone ratio was lower in varicocele rabbit compared with normal rabbits.Keywords: Estrogen-testosteron ratio, left artificial varicocele.